The Neutral Zone: Concept and Technique - Srivastava, Virag; Gupta, NK; Tandan, Amrit; Kaira, Laxman Singh; Chopra, Devendra (Journal of Orofacial Research, 2012)
When all of the remaining natural teeth are removed; there exists within the oral cavity a void that may be called the potential denture space. The denture space is bounded by the tongue, medially or internally, and by the muscles and tissues of the lips and cheeks laterally or externally. Within the denture space, there is an area that has been termed the neutral zone. The neutral zone is that area in the mouth where during function, the forces of the tongue pressing outward are neutralized by the forces of the cheeks and lips pressing inward. Since these forces are developed through muscles contraction during the various functions of chewing, swallowing and speaking, they vary in magnitude and direction in different individuals and in different periods of life. The way these forces are directed against the dentures will either help to stabilize them or will tend to dislodge them. In summary, the neutral zone philosophy is based on the concept that for each individual patient, there exists within the denture space a specific area where the function of the musculature will not unseat the denture and at the same time, where the forces generated by the tongue are neutralized by the forces generated by the lips and cheeks. Furthermore, denture stability is as much or more influenced by tooth position and flange contour as by any other factors.